Pengembangan Media Pembelajaran IPAS Berbasis Visual Art Dalam Meningkatkan Literasi Visual Mahasiswa Program Studi PGSD - Puji Winarti; Ridha Sarwono (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2022)
This study aims to develop a valid, practical, and effective Visual Art-based Natural and Social Sciences (IPAS) learning media in improving visual literacy of Elementary School Teacher Education (PGSD) students. The study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of two expert validators, namely material experts and media experts, and 30 PGSD students as product users. Data collection techniques include observation, interviews, questionnaires, documentation, and tests. Data analysis was carried out descriptively quantitatively using the percentage of validity, practicality, and N-Gain calculations. The results of the study showed that the learning media obtained a validity level of 92.00% from material experts and 93.60% from media experts with a very valid category. Student responses to the media reached 92.73% with a very practical category. The use of media also improved students' visual literacy skills, as demonstrated by an increase in the average score from 68.40 in the pretest to 86.70 in the posttest, with an N-Gain of 0.58 (moderate category). The results of this study indicate that visual art-based social studies learning media is suitable for use as an innovative learning tool to support the improvement of visual literacy in elementary school teacher education students.Keywords: learning media, social studies, visual art, visual literacy, ADDIE, elementary school teacher education